An Empirical Analysis of Payment Card Usage in India - Shilpa N.C.; Dr. Amulya M. (International Journal of Engineering and Management Research, 2019)
A paradigm shift in the modus operandi of commerce across the globe has been significantly influenced by the payment card industry with brisk strides in digital technology. The blooming payment card industry has escorted the prosperity in economic growth of most of the countries. Besides, there exists a divergent level in subsuming card payment by different countries due to distinct social, economic and cultural background. In India, excessive use cash payments are due to offbeat business models and varied distinction in literacy levels. This paper aims to analyse outstanding payment cards in India by examining the number of cards in operation and the value of transaction in the past decade. Data from RBI source is collected to analyse for a period of eight years (2011-2019). The research finds that credit card penetration has increased by threefold with average growth of 15% YoY and debit cards increased by more than threefold with average growth of 19% YoY during the period of analysis. Yet, asymmetry between debit cards holders and credit card holders exists in India indicating credit card is still niche product. This provides platform for the payment card industry to unleash the potential to tap market in India.